Kompetensi Profesional Guru PAK dalam Pembelajaran - Ranto Hutabarat; Dorlan Naibaho (Damai : Jurnal Pendidikan Agama Kristen dan Filsafat, 2025)
Professional competence is the ability that a teacher must have in carrying out his duties. In this day and age, teachers must have a variety of competencies related to teaching in order to increase students' interest in learning. Students are not active and are not quick to catch onsubject matter quickly becomes a big problem if PAK teachers do not have professional competence..For this reason, in the current digital era, teachers in schools need professional competence in achieving effective and efficient learning outcomes. This article uses descriptive qualitative research methods using various literature. The aim of this research is to describeprofessional competence that teachers must have. In conclusion, in order to succeed in learning activities in the digital era, teachers must have professional competence as one solution in facing learning challenges in the digital era.